1982
DOI: 10.1021/jm00352a036
|View full text |Cite
|
Sign up to set email alerts
|

2-Acetylpyridine thiosemicarbazones. 4. Complexes with transition metals as antimalarial and antileukemic agents

Abstract: Reaction of the 2-acetylpyridine thiosemicarbazones, 3-azabicyclo[3.2.2]nonane-3-thiocarboxylic acid 2-[1-(2-pyridyl)ethylidene]hydrazide (IIIa), its selenium analogue (IIIb), 1H-hexahydroazepine-1-thiocarboxylic acid 2-[1-(2-pyridyl)ethylidene]hydrazide (IV), and 1H-octahydroazocine-1-thiocarboxylic acid 2-[1-(2-pyridyl)ethylidene]hydrazide (V) with Cu(II), Ni(II), Fe(III), and Mn(II) salts gave crystalline complexes. Relative to the free ligands, these complexes show reduced antimalarial activity in mice inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
138
0
8

Year Published

1999
1999
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(147 citation statements)
references
References 0 publications
1
138
0
8
Order By: Relevance
“…This is due to remarkable biological activities observed for these compounds, which has since been shown to be related to their metal complexing ability. These compounds present a great variety of biological activity ranging from antitumour, fungicide, bactereocide, antiinflammatory, and antiviral activities [4][5][6][7][8]. We have previously examined the chelating behaviour of some NNS donor thiosemicarbazones having pyrazolone ring in several metal complexes with the object of gaining more information about their nature of coordination and related structural and spectral properties [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to remarkable biological activities observed for these compounds, which has since been shown to be related to their metal complexing ability. These compounds present a great variety of biological activity ranging from antitumour, fungicide, bactereocide, antiinflammatory, and antiviral activities [4][5][6][7][8]. We have previously examined the chelating behaviour of some NNS donor thiosemicarbazones having pyrazolone ring in several metal complexes with the object of gaining more information about their nature of coordination and related structural and spectral properties [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal complexes with heterocyclic thiosemicarbazone (TSC) ligands have attracted a great deal of research interest owing to their potential biological activity [1]. TSC ligands have invited considerable interest for a variety of reasons, such as variable bonding properties, because of the presence of several donor sites, structural diversity and pharmacological aspects.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that some drugs have increased the activity due to the metal complexes 9 . The number of metal chelates inhibits the growth of tumours 10 . In cancer treatments, it has been shown that the active species is not the thiosemicarbazone itself but a metal chelates of the thiosemicarbzones 11 .…”
Section: Introductionmentioning
confidence: 99%